2017
DOI: 10.14419/ijsw.v6i1.8529
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of thermophysical properties of alates (swarmers) termite wing as potential raw material for insulation

Abstract: Thermo physical properties of Alates (Swarmers) termite wing has been investigated. The result of our investigation shows the values of thermo physical parameters of the sample materials as 0.0403Wm-1K-1 being the mean thermal conductivity value, bulk density of 188. 8kgm-3 and thermal diffusively value being 8.2485 x 10-8m2s-1. The values are within the values for commonly used insulating materials. Comparing the rate of cooling as well as heat absorption into the material as lagging material with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The mean absorbed dose of BIR exposure is 147.3887 nGyh -1 while the mean annual effective dose equivalent of the mill is 0.1804 mSvy -1 . The absorbed doses in the entire rice mills are far higher than those reported in literature [8][9][10][11][12][13][14][15]19] and also above the recommended safe limit of 84.0 nGyh -1 [34,35]. Radiation levels increase as one gets closer to the source, so the high amount of absorbed radiation recorded in this work may have come from the rice grain and husks which the workers are always in contact with.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean absorbed dose of BIR exposure is 147.3887 nGyh -1 while the mean annual effective dose equivalent of the mill is 0.1804 mSvy -1 . The absorbed doses in the entire rice mills are far higher than those reported in literature [8][9][10][11][12][13][14][15]19] and also above the recommended safe limit of 84.0 nGyh -1 [34,35]. Radiation levels increase as one gets closer to the source, so the high amount of absorbed radiation recorded in this work may have come from the rice grain and husks which the workers are always in contact with.…”
Section: Resultsmentioning
confidence: 99%
“…Among the local studies is an evaluation of radiation indices and excess life cancer risk within Uyo, Unity Park, Uyo, Nigeria with a reported average dose rate of 0.116 μSvhr -1 [11]; measurements of surface dose rate of nuclear radiation in coastal areas of Akwa Ibom State, Nigeria where average dose rate of 0.12 μSvhr -1 (0.012 µRhr -1 ) was reported and which is below International Commission on Radiological Protection (ICRP) set standard of 1.0 mSvyr -1 [12]; the measurement of BIR from some selected refuse dumpsites in Yola Metropolis, Nigeria with the mean BIR values in all the five dumpsites as 0.132 ± 0.021 μSvhr -1 (0.015 ± 0.002 mRhr -1 ) [13]. The results showed that the average dose equivalent obtained for most locations within the study areas were above the standard background radiation of 0.013 mRhr -1 as recommended by ICRP.…”
Section: Introduction mentioning
confidence: 99%